Analytical investigations of concrete beams reinforced with FRP bars under static loads. (October 2022) - Sarhan, Mazin M.; Al-Zwainy, Faiq M.S.
Abstract: Fiber Reinforced Polymer (FRP) bars have appeared as a preferable alternative to ordinary steel bars in reinforced concrete (RC) members due to their higher ultimate tensile strength-to-weight ratio and corrosion resistance. The previous studies have mainly focused on laboratory tests and finite element modeling approaches for FRP-RC beams; however, only limited analytical studies have been conducted. Therefore, this study was designed to present analytical investigations of full-scale concrete beams longitudinally reinforced with Glass-Fiber Reinforced Polymer (GFRP) bars. The Strips Analysis Method (S-A-M) was used to implement the analytical investigations using stress–strain models for concrete and reinforcement. The beams, having the cross-sectional dimensions of 150 mm width × 200 mm height, were statically analyzed under different-point bending. The analytical results were verified with the results of experimentally tested GFRP-RC beams, and the outcomes showed excellent agreements. Also, the analytical method used in this study exhibited much efficiency and reliability compared with the traditional procedures used for the analysis of ordinary reinforced concrete members. A parametric study was, in addition, conducted to investigate the effects of concrete compressive strength, different-point bending, and scale of beams on the performance of GFRP-RC beams. It was found that the structural efficiency of GFRP-RC beams can be enhanced with the increase in concrete compressive strength and significantly influenced by the scale size of beams.